Strong interaction of a quantum dot with the photon reservoir in one-dimensional photonic crystals. Issue 1 (April 2021) - Gainutdinov, R Kh; Nabieva, L J; Garifullin, A I; Mutygullina, A A
Abstract: Quantum fluctuations as a process of the self-interaction of a system lead to a shift of the energy levels and are usually described by the self-energy function. Here quantum fluctuations caused by the interaction of a quantum dot coupled with an one-dimensional photonic crystal's cavity with the photon reservoir are discussed. It is shown that this interaction can lead to a significant increase in quantum fluctuations. The self-interaction is of interest for solving problems of decreasing decoherence and dephasing of qubit for quantum computation.